The role of corifollitropin alfa in controlled ovarian stimulation for IVF in combination with GnRH antagonist - Seyhan A; Ata B (Dove Medical Press, 2011)
Ayse Seyhan, Baris AtaDivision of Reproductive Endocrinology and Infertility, Department of Obstetrics and Gynecology, McGill University, Montreal, QC, CanadaAbstract: Corifollitropin alfa is a synthetic recombinant follicle-stimulating hormone (rFSH) molecule containing a hybrid beta subunit, which provides a plasma half-life of ∼65 hours while maintaining its pharmocodynamic activity. A single injection of corifollitropin alfa can replace daily FSH injections for the first week of ovarian stimulation for in vitro fertilization. Stimulation can be continued with daily FSH injections if the need arises. To date, more than 2500 anticipated normoresponder women have participated in clinical trials with corifollitropin alfa. It is noteworthy that one-third of women did not require additional gonadotropin injections and reached human chorionic gonadotropin criterion on day 8. The optimal corifollitropin dose has been calculated to be 100 µg for women with a body weight ≤ 60 kg and 150 µg for women with a body weight >60 kg, respectively. Combination of corifollitropin with daily gonadotropin-releasing hormone antagonist injections starting on stimulation day 5 seems to yield similar or significantly higher numbers of oocytes and good quality embryos, as well as similar ongoing pregnancy rates compared with women stimulated with daily rFSH injections. Stimulation characteristics, embryology, and clinical outcomes seem consistent with repeated corifollitropin-stimulated assisted reproductive technologies cycles. Multiple pregnancy or ovarian hyperstimulation syndrome rates with corifollitropin were not increased over daily FSH regimen. The corifollitropin alfa molecule does not seem to be immunogenic and does not induce neutralizing antibody formation. Drug hypersensitivity and injection-site reactions are not increased. Incidence and nature of adverse events and serious adverse events are similar to daily FSH injections. Current trials do not provide information regarding use of corifollitropin alfa in anticipated hyper- and poor responders to gonadotropin stimulation. Although corifollitropin alfa is unlikely to be teratogenic, at the moment data on congenital malformations is missing.Keywords: follicle-stimulating hormone, long acting, controlled ovarian hyperstimulation, in vitro fertilization, assisted reproduction